IMPACT OF NURSE RESIDENCY PROGRAMS ON RETENTION AND SATISFACTION - Manal Ghazi Alharthi, Halima Abed Ulkader Oth Man, Ahmed Awadh Gazi Alotaibi, Faisal Dhedan Mufareh Alenzi, Nahid Husayn Hamd Khardali, Salha Ibrahim Ageel, Badriah Saleh Colaib Jawhar,; Norah Mulfi Nuwaydis Alrashdi, Kot Dabis Saleh Zibnah, Mohammed Olayan Burayk Alrashdi, Bandar Yahya Ahamed Alharbi, Mohammad Obeid Aldosari (Chelonian Research Foundation, 2022)
An analysis and discourse on the establishment of nurse residency programs using the suggestions from accrediting organizations to showcase the worth of the organization. Implementing an authorized framework for developing nurse residency programs showcases the organizational influence and worth by guaranteeing the integration of evidence-based constructions and plans to achieve patient safety and other company objectives, fulfill healthy workplace goals, reduce turnover, and enhance nursing job satisfaction. The analysis encompasses an overview of the Institute of Medicine study, nurse recruitment and retention, and the related expenses. Additionally, it contains the guidance provided by the Nurses Credentialing Center Practice Conversion Programme for the development of the residency program. An examination of a sample curriculum and analysis of indicators for improvement provide evidence that an effective transition to nursing practice equips nurses with the necessary confidence and proficiency to offer high-quality patient care. Keywords: nurse residency, programs, retention, satisfaction, patient care.